Deforestation-forestation - Angelsen, A. (2001)
The article first reviews rates and definitions of tropical deforestation and the environmental implications in terms of climate change, biodiversity loss, and reduced supply of forest products. Tropical deforestation and other land use changes contributed about 20% of the global anthropogenic CO2 emissions during the 1990s. The main focus of the article is on the driving forces of deforestation. The starting point is to investigate which factors make deforestation the most attractive option to farmers, private companies and governments – the immediate causes of deforestation. These include high agricultural prices, easy access to forests and lack of alternative employment. The effects of other factors such as agricultural technologies, poverty and property rights appear to be more context specific. These factors are determined by broader forces, the underlying causes of deforestation, but the links are complex making global generalizations difficult. In fact, the empirical foundation for much of the conventional wisdom on the underlying causes is surprisingly weak. The article also underscores to the political economy dimension of tropical deforestation. Different groups have unequal access to the forest and policies are often designed to benefit elite interests.